Penerapan Metode Design Thinking dalam Perancangan Desain Antarmuka Pada Aplikasi E-Modul Model Pembelajaran Li-Pro-GP - Aldhy Sidqi (Jurnal Repositor, 2026)
This research focuses on designing the user interface of a web-based E-Module application using the Design Thinking method to enhance user experience. The main challenge addressed is creating an intuitive and easy-to-use interface that meets user needs. The method used consists of five stages: empathize (understanding user needs), define (defining the problem), ideate (generating ideas), prototype (creating a prototype), and test (testing) using the System Usability Scale (SUS) to measure the application's usability. The goal of this research is to produce an E-Module application prototype with high usability based on SUS testing results. The test results show that the prototype received an average SUS score of 86, graded as B, reflecting a high level of user satisfaction, with users feeling comfortable and finding the application easy to use. However, the research did not achieve an A score on the SUS, so future studies are recommended to involve more respondents for testing and to further develop the prototype to achieve optimal usability